2014
DOI: 10.1007/s10654-014-9893-4
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in health and mortality in Moscow and Denmark

Abstract: In high income countries females outlive men, although they generally report worse health, the so-called male–female health-survival paradox. Russia has one of the world’s largest sex difference in life expectancy with a male disadvantage of more than 10 years. We compare components of the paradox between Denmark and Moscow by examining sex differences in mortality and several health measures. The Human Mortality Database and the Russian Fertility and Mortality Database were used to examine sex differences in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 47 publications
3
29
0
7
Order By: Relevance
“…We observed better physical functioning among men than women in cross-sectional analyses, consistent with a previous cross-sectional study of adults aged 55–89 years in Denmark and Russia using the SF-36 PF subscale [41]. Men have been reported to have lower prevalence of functional limitations and disability consistently across many countries including continental Europe, the UK and the US [10, 42].…”
Section: Discussionsupporting
confidence: 89%
“…We observed better physical functioning among men than women in cross-sectional analyses, consistent with a previous cross-sectional study of adults aged 55–89 years in Denmark and Russia using the SF-36 PF subscale [41]. Men have been reported to have lower prevalence of functional limitations and disability consistently across many countries including continental Europe, the UK and the US [10, 42].…”
Section: Discussionsupporting
confidence: 89%
“…Previous Danish studies have indicated that ‘healthy’ women volunteers are less healthy than males, as they more often are medically treated for other diseases and have higher hospitalization rates in the years preceding the diagnosing of hypothyroidism . However, the authors concluded that this selection did not have large impact on study results …”
Section: Discussionmentioning
confidence: 91%
“…Previous surveys also reported a lower degree of wellness and health in women as expressed in terms of higher hospitalization rates and medical prescription prevalences, lower SF‐36 item scores, ameliorated physical performance, and lower degree of happiness …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, migrants represent a heterogeneous group and differ in their origin, their cultural backgrounds, their motives to migrate, their duration of stay in the host country, their legal status, their degree of integration, their demographic behaviour, and many other characteristics (Lindert et al 2008;Norredam 2011;Neuhauser and Razum 2008). They differ both among themselves as well as from the society of origin and the host society.…”
Section: Migration Background and Health In A Household Contextmentioning
confidence: 99%